Human telomerase inhibition by substituted acridine derivatives - Harrison, R. John; Gowan, Sharon M.; Kelland, Lloyd R.; Neidle, Stephen (Bioorganic & medicinal chemistry letters, 1999)
A series of 3,6-disubstituted acridine derivatives have been rationally designed as telomerase inhibitors. They have been designed on the basis that inhibition of telomerase occurs by stabilising G-quadruplex structures formed by the folding of telomeric DNA. The most potent inhibitors have IC 50 values against telomerase of between 1.3 and 8 μM, comparable to their cytotoxicity in ovarian cancer cell lines.